2023
DOI: 10.1200/jco.22.01935
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib Versus Best Available Therapy for Polycythemia Vera Intolerant or Resistant to Hydroxycarbamide in a Randomized Trial

Abstract: PURPOSE Polycythemia vera (PV) is characterized by JAK/STAT activation, thrombotic/hemorrhagic events, systemic symptoms, and disease transformation. In high-risk PV, ruxolitinib controls blood counts and improves symptoms. PATIENTS AND METHODS MAJIC-PV is a randomized phase II trial of ruxolitinib versus best available therapy (BAT) in patients resistant/intolerant to hydroxycarbamide (HC-INT/RES). Primary outcome was complete response (CR) within 1 year. Secondary outcomes included duration of response, even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 19 publications
4
14
0
3
Order By: Relevance
“…Our take on the RESPONSE and MAJIC-PV clinical trials is that they clearly show salvage value for ruxolitinib, in the presence of symptoms reminiscent of post-PV myelofibrosis and, in patients suffering from drug-refractory pruritus or symptomatically enlarged spleen. 141 As was reported in the MAJIC-PV trial, 145 we and others have also shown an association between JAK2 inhibitor-induced response and longer survival, in the context of myelofibrosis. [152][153][154][155][156] However, such observations might represent response-enabled identification of long-lived patients, rather than a reflection of diseasemodifying activity for a specific drug.…”
Section: Recommendationssupporting
confidence: 71%
See 1 more Smart Citation
“…Our take on the RESPONSE and MAJIC-PV clinical trials is that they clearly show salvage value for ruxolitinib, in the presence of symptoms reminiscent of post-PV myelofibrosis and, in patients suffering from drug-refractory pruritus or symptomatically enlarged spleen. 141 As was reported in the MAJIC-PV trial, 145 we and others have also shown an association between JAK2 inhibitor-induced response and longer survival, in the context of myelofibrosis. [152][153][154][155][156] However, such observations might represent response-enabled identification of long-lived patients, rather than a reflection of diseasemodifying activity for a specific drug.…”
Section: Recommendationssupporting
confidence: 71%
“…141,143 The benefit of ruxolitinib as salvage therapy for HU-resistant/intolerant PV was again demonstrated in another randomized phase-2 study (MAJIC-PV; N = 180) 145 ; CR was reported in 43% of patients on ruxolitinib versus 26% on BAT; in addition, ruxolitinib-treated patients displayed longer duration of response and better control of symptoms; event-free survival at 1 year was reported to be superior in patients with CR; ruxolitinib therapy was also associated with a decline in JAK2V617F allele burden and was associated with superior event-free and overall survival. 145 The efficacy of oral busulfan (dosed at 2-4 mg/day) in patients with advanced PV or ET refractory or intolerant to hydroxyurea was assessed in two recent studies 146,147 ; in one study of 36 patients with a treatment duration of 256 days, which included 15 patients with PV, 146 complete hematological response was reported in 83% of the patients, which was sustained in the majority of the patients at 2 years. Busulfan was discontinued in 18 (67%) patients because of unmaintained remission, which is a unique feature of busulfan treatment response in patients with MPN; and 33% of informative cases demonstrated partial molecular response.…”
Section: Treatment Choices Beyond Hydroxyurea or Pegylated Interferonmentioning
confidence: 93%
“…Thromboembolic event-free survival was significantly improved with ruxolitinib (hazard ratio [HR], 0.56; 95% CI, 0.32 to 1.00; p = .05). 27 The overall safety profile observed in the study was consistent with that observed in prior studies of ruxolitinib, with no new safety signals identified. 21,22,25,28 Overall, the results from this observational study build on the data and evidence from the earlier pivotal studies RESPONSE and RESPONSE-2 and provide real-world evidence of the efficacy and safety of ruxolitinib in clinical practice.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, conventional anti-platelet therapy does not fully mitigate thrombotic risk and cytoreductive therapy has shown limited potential to alter natural history of the disease to date 45 . Recent data suggest 46 that disease course may be modified with targeted treatments, however options remain limited, with incomplete understanding of why patients fail first line therapy with few available alternatives. One approach that is increasingly recognized as highly valuable in identifying novel therapeutic targets as well as molecular markers of disease (especially at a systems level) is to leverage pertinent multi-omic [47][48][49] datasets.…”
Section: Discussionmentioning
confidence: 99%